Identifying anti-Blackness and committing to Pro-Blackness in early literacy pedagogy and research: A guide for child care settings, schools, teacher preparation programs, and researchers. (December 2022) - Wynter-Hoyte, Kamania; Braden, Eliza; Boutte, Gloria; Long, Susi; Muller, Meir
This article is written for educators who serve as teachers, administrators, policy-makers in childcare settings, schools, classrooms, teacher preparation programs, programs that prepare educational researchers, and universities. Its purpose is to provide background, rationale, and support for individuals within those institutions to address the need to identify and counter anti-Black racist structures, policies, and practice within and beyond educational spaces. While the focus is on spaces connected to early literacy education, the content of this article will also be useful for educators and educational researchers in other areas of education. After providing a framework in Critical Race and Black Critical theories and addressing attempts to interrupt and take down any teaching about racial histories or contemporary issues, the authors provide extensive lists of questions that can be used for educational stakeholders to root out anti-Blackness in their institutions. A few of the elements of institutions addressed in this article include: early literacy and teacher preparation curriculum; assessments and testing; attitudes and perceptions; and hiring and retaining Black faculty and administration. Written with love and a sense of urgency and joy in the process of change, this article will provide impetus but also explicit guidance for educators to examine and analyze elements of their own institutions and use findings to engage in change that centers the excellence, joy, resistance, and resilience of Black people.